Effectiveness of pure argon for renal transplant preservation in a preclinical pig model of heterotopic autotransplantation. Issue 1 (December 2016) - Faure, Alice; Bruzzese, Laurie; Steinberg, Jean-Guillaume; Jammes, Yves; Torrents, Julia; Berdah, Stephane; Garnier, Emmanuelle; Legris, Tristan; Loundou, Anderson; Chalopin, Matthieu; Magalon, Guy; Guieu, Regis; et al.
Abstract Background In kidney transplantation, the conditions of organ preservation following removal influence function recovery. Current static preservation procedures are generally based on immersion in a cold-storage solution used under atmospheric air (approximately 78 kPa N2, 21 kPa O2, 1 kPa Ar). Research on static cold-preservation solutions has stalled, and modifying the gas composition of the storage medium for improving preservation was considered. Organoprotective strategies successfully used noble gases and we addressed here the effects of argon and xenon on graft preservation in an established preclinical pig model of autotransplantation. Methods The preservation solution Celsior saturated with pure argon (Argon-Celsior) or xenon (Xenon-Celsior) at atmospheric pressure was tested versus Celsior saturated with atmospheric air (Air-Celsior). The left kidney was removed, and Air-Celsior (n = 8 pigs), Argon-Celsior (n = 8) or Xenon-Celsior (n = 6) was used at 4 °C to flush and store the transplant for 30 h, a duration that induced ischemic injury in our model when Air-Celsior was used. Heterotopic autotransplantation and contralateral nephrectomy were performed. Animals were followed for 21 days. Results The use of Argon-Celsior vs. Air-Celsior: (1) improved function recovery as monitored via creatinine clearance, the fraction of excreted sodium and tubulopathy duration; (2) enabled diuresis recovery 2–3 days earlier; (3) improved survival (7/8 vs. 3/8 pigs survived at postoperative day-21); (4) decreased tubular necrosis, interstitial fibrosis, apoptosis and inflammation, and preserved tissue structures as observed after the natural death/euthanasia; (5) stimulated plasma antioxidant defences during the days following transplantation as shown by monitoring the "reduced ascorbic acid/thiobarbituric acid reactive substances" ratio and Hsp27 expression; (6) limited the inflammatory response as shown by expression of TNF-alpha, IL1-beta and IL6 as observed after the natural death/euthanasia. Conversely, Xenon-Celsior was detrimental, no animal surviving by day-8 in a context where functional recovery, renal tissue properties and the antioxidant and inflammation responses were significantly altered. Thus, the positive effects of argon were not attributable to the noble gases as a group. Conclusions The saturation of Celsior with argon improved early functional recovery, graft quality and survival. Manipulating the gas composition of a preservation medium constitutes therefore a promising approach to improve preservation.